Simplifying the deployment of OGC web processing services (WPS) for environmental modelling – Introducing Tethys WPS Server. (May 2019) - Qiao, Xiaohui; Li, Zhiyu; Ames, Daniel P.; Nelson, E. James; Swain, Nathan R.
Abstract: Developing a complex environmental modelling web application or "web app" can be a challenging task that requires integration of various models and data sources with ever-changing Internet technologies. Service-Oriented Architecture (SOA) has been shown to be useful for building complex modelling workflows. However, compared with other types of web services, such as those for data delivery and mapping, the implementation of Open Geospatial Consortium (OGC) web processing services (WPS) for environmental modelling and data analysis is not very common. This problem stems, in part, from the lack of tools to simplify the development and deployment of WPS for the broad and complex set of environmental modelling applications. This paper presents the development and testing of a ready-to-use WPS implementation called Tethys WPS Server, which provides a formalized way to expose web app functionality as standardized WPS alongside a web app's graphical user interface. The WPS server is created based on Tethys Platform by leveraging PyWPS. Three Tethys web apps are developed to demonstrate how web app functionality(s) can be exposed as WPS using Tethys WPS Server, and to show how these WPS can be coupled to build a complex modelling web app. Moreover, we demonstrate that the services hosted on Tethys WPS Server follow OGC standards correctly and can be used successfully by third party applications and clients that support the OGC WPS specification. Highlights: Tethys WPS Server was developed and tested to expose web app functionality using the OGC WPS standard. Workshop results show that Tethys WPS Server simplifies developing and deploying OGC WPS services. Two demonstration web apps are extended using Tethys WPS Server for watershed delineation and reservoir volume calculation. A HydroProspector app for identifying potential hydropower reservoir sites is developed using WPS services provided via Tethys WPS Server.